2017
DOI: 10.3390/ijms18091833
|View full text |Cite
|
Sign up to set email alerts
|

miR-145-5p Suppresses Tumor Cell Migration, Invasion and Epithelial to Mesenchymal Transition by Regulating the Sp1/NF-κB Signaling Pathway in Esophageal Squamous Cell Carcinoma

Abstract: MicroRNAs (miRNAs) play important roles in the progression of human cancer. Although previous reports have shown that miR-145-5p is down-regulated in esophageal squamous cell carcinoma (ESCC), the roles and mechanisms of down-regulation of miR-145-5p in ESCC are still largely unknown. Using microRNA microarray and Gene Expression Omnibus (GEO) datasets, we confirmed that miR-145-5p was down-regulated in ESCC tissues. In vitro assays revealed that ectopic miR-145-5p expression repressed cell proliferation, migr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
55
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(58 citation statements)
references
References 35 publications
3
55
0
Order By: Relevance
“…Xia et al (49) reported that the downregulation of SP1 could reduce the proliferation rate of ovarian cancer cells and restrain tumor metastasis. Mei et al (50) revealed that certain miRNAs may suppress the multiplication, migration and EMT of esophageal cancer cells by targeting SP1. Notably, it was discovered that the overexpression of miR-539 inhibited the effects of SP1 on Pca cell lines, and that SP1-silencing reversed the effect of low expression of miR-539, showing that miR-539 was involved in the occurrence and development of Pca through targeting SP1.…”
Section: Discussionmentioning
confidence: 99%
“…Xia et al (49) reported that the downregulation of SP1 could reduce the proliferation rate of ovarian cancer cells and restrain tumor metastasis. Mei et al (50) revealed that certain miRNAs may suppress the multiplication, migration and EMT of esophageal cancer cells by targeting SP1. Notably, it was discovered that the overexpression of miR-539 inhibited the effects of SP1 on Pca cell lines, and that SP1-silencing reversed the effect of low expression of miR-539, showing that miR-539 was involved in the occurrence and development of Pca through targeting SP1.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that miR-145-5p expression is decreased in breast cancer and esophageal carcinoma, and its downregulation is associated with distal metastasis, tumor differentiation, and poor survival in GC patients [29][30][31]. miR-145-5p suppresses the proliferation and invasion by targeting SOX2 or SP1 [29,31], and promotes GC differentiation by targeting KLF5 [30]. Herein, we found that miR-145-5p expression was downregulated in GC tissue samples, and its low expression was an independent prognostic factor of poor survival in GC patients.…”
Section: Discussionmentioning
confidence: 99%
“…The expression of both miR-143 and miR-145 is reduced in esophageal squamous cell carcinoma clinical samples [71,72], where their overexpression was shown to downregulate mesenchymal markers, reducing cell migration and metastatic ability [71,72]. miR-145 ectopic expression inhibited cell migration by reducing the levels of FASCIN1 (FSCN1), an actin bundling protein involved in cytoskeletal dynamics, and regulating several EMT features in several breast cancer cell lines [73].…”
Section: Mir-143 and -145 And Emtmentioning
confidence: 99%
“…Finally, proteins involved in cell-cell adhesion and cell motility can be targeted by both microRNAs. For example, the cell-cell adhesion protein JAM-A [102] and the actin bundling protein FSCN1 [55,72,[102][103][104][105] have both been described as miR-145 targets, suggesting inhibition of cell adhesion and movement. Indeed, overexpression of miR-145 in breast cancer cell lines decreased actin stress fibers, and miR-143 was shown to regulate ADDUCIN 3 [106] and FIBRONECTIN [21,49], leading to reduced cell migration.…”
Section: Proposed and Validated Targets Of The Micrornasmentioning
confidence: 99%